PEMBUATAN ASPAL EMULSI YANG TAHAN-SIMPAN - Leksminingsih Leksminingsih (Jurnal Kimia Terapan Indonesia, 2000)
Cold Mixed Asphalt Emulsion generally used for roadmaintenance, such as film Slurry Seal to cover cracked roadsurface, Patching, Dense Graded Emulsion Mixed (DGEM) andOpen Graded Emulsion Mixed (OGEM) for road pavement.One of several obstacles using asphalt emulsion, is the shorttime of storage stability, less than three months. This problem hasan effect to road maintenance especially for District road thathave light traffic.Asphalt emulsion is made 0f: bitumen, kerosene, emulsifier,HCI, CaCl, and watel: Asphalt emulsion has pH of 2,5 to 4%.To mix the component of asphalt emulsion a Colloid Millequipment is used, which has a rotation of 1000 until 6000 rpm,and has a gap between rotor and stator of250 um unti/500 um,so the asphalt emulsion product has a particle > 250 ~Wl.To make a longer storage stability oj asphalt emulsion, usingtwo method s i.e:1. By experiment, to make various contents of asphalt emulsionbase materials and do the test using a standard test oj ASTMD 244-90 until six months.2. To make various contents of asphalt emulsion base materials,not only measure the rate stability by Stoke 'sformula, but alsoperform the test until six months.The result of method 1(1) the components of asphalt emulsionare: 65% of bitumen, 2,8% of kerosene, 0,48% of emulsifier.0,48% of HCI, 0,3% of CaCl, and 30,94% of water, after sixmonths the test result still hove comply with the spesijication ofAASHTO M 208.The result of method 2(2), the rate stabiliy have aroun d of18 x 10-7 until 35 x 10-7 cm/second,From ten formulas using method 2, three still stand until sixmonths. The selected formula was made in a drum, and was testeduntil six months.